1994
DOI: 10.1002/mpo.2950220102
|View full text |Cite
|
Sign up to set email alerts
|

Second malignant tumors following treatment during childhood and adolescence for cancer

Abstract: Many pediatric and adolescent cancer patients are treated with carcinogenic chemotherapeutic agents and radiation therapy to achieve permanent control of their malignancy. These modalities may induce a new cancer in the successfully treated patient. To identify disease and treatment factors which increased the risk of occurrence of a second malignant tumor following modern treatment for cancer during childhood or adolescence, we reviewed the courses of 1,406 previously untreated patients who were less than 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…Actuarial rates have ranged from 3-13% at 20 -30 years of follow-up. 6,8,10,18,22,[25][26][27] Higher rates are associated with single-institution studies, as is ours, whereas lower rates are associated with larger studies involving multiple institutions. Additional reasons may account for the higher risk estimate in the current study.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Actuarial rates have ranged from 3-13% at 20 -30 years of follow-up. 6,8,10,18,22,[25][26][27] Higher rates are associated with single-institution studies, as is ours, whereas lower rates are associated with larger studies involving multiple institutions. Additional reasons may account for the higher risk estimate in the current study.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies differ on the importance of age and gender as risk factors. 22,26,27,29 For example, Neglia et al 22 found female gender to be a significant risk factor, whereas Olsen et al 29 reported that male gender was a risk factor. In addition, de Vathaire et al 26 reported that older age was a risk factor, whereas a younger age was found to be a risk factor in the Neglia et al study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23][24] We found only four studies that reported the number of patients with a primary diagnosis of AML who were in the cohort; either no second cancer or only one second cancer was reported for these four studies with a small number of patients (38 to 163 patients). [25][26][27][28] Comparison of the findings of these four studies with those of our study is not possible because information about the person-years at risk or the cumulative incidence of second cancer in the survivors of AML was not reported.…”
Section: Leukemiamentioning
confidence: 82%